Congress of Neurological Surgeons Systematic Review and Evidence-Based Guideline on the Role of Cranial Molding Orthosis (Helmet) Therapy for Patients With Positional Plagiocephaly. Issue 5 (November 2016) - Tamber, Mandeep S.; Nikas, Dimitrios; Beier, Alexandra; Baird, Lissa C.; Bauer, David F.; Durham, Susan; Klimo, Paul; Lin, Alexander Y.; Mazzola, Catherine; McClung-Smith, Catherine; Mitchell, Laura; Tyagi, Rachana; et al.
Abstract : BACKGROUND: No evidence-based guidelines exist on the role of cranial-molding orthosis (helmet) therapy for patients with positional plagiocephaly. OBJECTIVE: To address the clinical question: "Does helmet therapy provide effective treatment for positional plagiocephaly?" and to make treatment recommendations based on the available evidence. METHODS: The US National Library of Medicine Medline database and the Cochrane Library were queried by using MeSH headings and key words relevant to the objective of this systematic review. Abstracts were reviewed, after which studies meeting the inclusion criteria were selected and graded according to their quality of evidence (Classes I-III). Evidentiary tables were constructed that summarized pertinent study results, and, based on the quality of the literature, recommendations were made (Levels I-III). RESULTS: Fifteen articles met criteria for inclusion into the evidence tables. There was 1 prospective randomized controlled trial (Class II), 5 prospective comparative studies (Class II), and 9 retrospective comparative studies (Class II). CONCLUSION: There is a fairly substantive body of nonrandomized evidence that demonstrates more significant and faster improvement of cranial shape in infants with positional plagiocephaly treated with a helmet in comparison with conservative therapy, especially if the deformity is severe, provided that helmet therapy is applied during the appropriate period of infancy. Specific criteria regarding the measurement and quantification of deformity and the most appropriate time window in infancy for treatment of positional plagiocephaly with a helmet remains elusive. In general, infants with a more severe presenting deformity and infants who are helmeted early in infancy tend to have more significant correction (and even normalization) of head shape. The full guidelines document can be located athttps://www.cns.org/guidelines/guidelines-management-patients-positional-plagiocephaly/Chapter_5 .